Immersive and Interactive 360 Video Editing for Virtual Reality - Nobbs, Connor (Wellington Faculty of Engineering Symposium, 2023)
360 videos are an increasingly more common way of viewing content on the internet. They are also best viewed in virtual reality, as it offers a higher level of immersion that suits the video format in comparison to a standard computer monitor. The usage of virtual reality is also on the rise both for entertainment and education. Logically, editing 360 videos in virtual reality would offer this same immersion, potentially allowing for a better final video. Current video editing tools are either not available for virtual reality or only offer limited functionality. Many of these tools also do not handle the unique challenge that 360 videos pose. Making edits with these limitations can lead to interrupted workflows and mis-edits. During this project a prototype framework was built. This prototype allows for pixel-wise 360 image and video editing, previously untested in virtual reality. The project was built in Unity engine and uses two C++ implementations of video editing techniques: colour editing that differentiates between foreground and background, and a simple usage of optical flow that allows a user drawn piece of ‘graffiti’ to remain consistently placed between video frames. User testing was done to test both the user experience and effectiveness of the prototype, as well as getting aesthetic opinions on the video edits. This user testing as well as other limitations of the prototype have been anonymised and documented, giving a clear path for future work.